Mapping of proteomic lysate of a MCF-7 cancer cell line for the identification of potential markers for breast cancer - V. E. Shevchenko; M. A. Taipov; S. V. Kovalev; N. E. Arnotskaya; O. M. Pavlova; I. A. Kudryavtsev; Z. N. Nikiforova (Опухоли женской репродуктивной системы)
Mass spectrometric mapping of proteomic lysate of a MCF-7 cancer cell line was carried out, which identified 153 proteins having molecular weights of 5000 to 630000 Da, a high proportion of which was cytoplasmic and nuclear proteins. The latter accounted for 60 % of their total number whereas the proportion of extracellular and membrane proteins constituted 13 %. After using some selection criteria to analyze the findings, the authors present a list of 31 potential biomarkers and describe 12 promising breast anticancer therapeutic targets.